INFLUENCE OF Breg AND IL-10 UPON HUMORAL IMMUNE RESPONSE - M. V. Gavrilova; N. A. Snegireva; E. V. Sidorova (Медицинская иммунология, 2016)
B regulatory cells (Bregs) are shown to downregulate autoimmune and inflammation processes. Their modifying effects depend on IL-10 secretion. A role of Bregs in development of humoral immune response was not investigated. Influence of Bregs and IL-10 upon in vitro response of murine B1 and B2 cells to T-dependent and T-independent antigens was studied in a model system. A water-soluble sheep erythrocyte antigen was used as a T-dependent antigen, whereas LPS was applied as a type 1 T-independent antigen, and polyvinylpirrolidone and alpha(1→3)dextran were added as type 2 T-independent antigens. В1and B2 lymphocytes were isolated from, respectively, peritoneal cavity and spleen of CBA mice. The cells were cultured in RPMI1640 medium with 10% of FCS supplemented with appropriate antigens and IL-10. The numbers of antibody- and total Ig-forming cells were determined by ELISPOT method.The erythrocyte antigen induced an increase of antibody- and total Ig-forming cell numbers in cultured B1 and B2 cell populations. IL-10 addition caused reduction of antibody- and total Ig-forming cells by 27%. Similarly, IL-10 caused a drop in antibody- and total Ig-forming cells in LPS-stimulated B2 cell cultures by 75%, as well as 50 per cent decrease in numbers of antibody-forming cells in B-1 cell cultures when induced by the type 2 T-independent antigens.To assess functional activity of Bregs, the cells were isolated from peritoneal cavity and spleen of CBA mice. Total yields of Bregs were 20-fold increased upon activation of B cells with LPS, ionomycin and phorbol ester (from 4% to 96%). IgM was the main immunoglobulin isotype secreted by the Bregs. 96% of activated Bregs produced IL-10. About 12% of the cells were shown to produce immunoglobulins. This finding suggests that some of Bregs synthesize both IL-10 and immunoglobulins.To study distant effect of Bregs upon immune response, the splenocyte culture of xid CBA/N mice were tested in Transwells with enriched Bregs. It was revealed that the Bregs caused inhibition of both specific and polyclonal immune response to the water-soluble sheep erythrocyte antigen. Hence, Bregs are shown to participate in humoral immune response, probably, by suppressing functional activity of splenocytes from CBA/N mice to T-dependent antigen. IL-10 secreted by Bregs may play a sufficient role in these regulatory effects.